Low Tidal Volumes Are Associated With Slightly Improved Oxygenation in Patients Having Cardiac Surgery: A Cohort Analysis. (May 2020) - Jia, Yuan; Leung, Steve M.; Turan, Alparslan; Artis, Amanda S.; Marciniak, Donn; Mick, Stephanie; Devarajan, Jagan; Duncan, Andra E.
Abstract : BACKGROUND: Mechanical ventilation with low tidal volumes appears to provide benefit in patients having noncardiac surgery; however, whether it is beneficial in patients having cardiac surgery is unclear. METHODS: We retrospectively examined patients having elective cardiac surgery requiring cardiopulmonary bypass through a median sternotomy approach who received mechanical ventilation with a single lumen endotracheal tube from January 2010 to mid-August 2016. Time-weighted average tidal volume (milliliter per kilogram predicted body weight [PBW]) during the duration of surgery excluding cardiopulmonary bypass was analyzed. The association between tidal volumes and postoperative oxygenation (measured by arterial partial pressure of oxygen (PaO2 )/fraction of inspired oxygen ratio [PaO2 /FIO2 ]), impaired oxygenation (PaO2 /FIO2 <300), and clinical outcomes were examined. RESULTS: Of 9359 cardiac surgical patients, larger tidal volumes were associated with slightly worse postoperative oxygenation. Postoperative PaO2 /FIO2 decreased an estimated 1.05% per 1 mL/kg PBW increase in tidal volume (97.5% confidence interval [CI], −1.74 to −0.37; P Bon = .0005). An increase in intraoperative tidal volumes was also associated with increased odds of impaired oxygenation (odds ratio [OR; 97.5% CI]: 1.08 [1.02–1.14] per 1 mL/kg PBW increase in tidal volume; P Bon = .0029), slightly longer intubation time (5% per 1 mL/kg increase in tidal volume (hazard ratio [98.33% CI], 0.95 [0.93–0.98] per 1 mL/kg PBW; P Bon < .0001), and increased mortality (OR [98.33% CI], 1.34 [1.06–1.70] per 1 mL/kg PBW increase in tidal volume; P Holm = .0144). An increase in intraoperative tidal volumes was also associated with acute postoperative respiratory failure (OR [98.33% CI], 1.16 [1.03–1.32] per 1 mL/kg PBW increase in tidal volume; P Holm = .0146), but not other pulmonary complications. CONCLUSIONS: Lower time-weighted average intraoperative tidal volumes were associated with a very modest improvement in postoperative oxygenation in patients having cardiac surgery.